DFT investigation of the potential of porous cages for the catalysis of ammonia borane dehydrogenation - Pal, Amrita; Vanka, Kumar (Chemical Communications, 2011)
Full DFT based quantum mechanical studies reveal that zero dimensional porous structures, especially the newly proposed phosphorus incorporated organic cages, can be excellent catalysts for the dehydrogenation of ammonia borane.

Exploring the effectiveness of different Lewis pair combinations in caged structures for the catalysis of ammonia borane dehydrogenation: a DFT study - Pal, Amrita; Vanka, Kumar (Physical Chemistry Chemical Physics, 2013)
Zero dimensional cage structures containing four phenyl rings separated by imine linkers have recently been synthesized. In the current work, through a computational investigation using density functional theory (DFT), we demonstrate that modifying such cages by replacing the 2, 4, 6 carbon atoms in the phenyl rings to yield new rings, as well as replacing the imine moiety in the linker by other electronegative atoms, can yield interesting new cages that can be reactive in catalysing reactions such as the dehydrogenation of ammonia borane-an important reaction in hydrogen storage research. Specifically, it is predicted that phosphorus-nitrogen pairs (phosphorus in the 2, 4, 6 positions in the ring, nitrogen in the linker position), germanium-nitrogen and germanium-phosphorus pair combinations would lead to effective Lewis pairs that can work in tandem to dehydrogenate ammonia borane efficiently under room temperature conditions.

Proposing late transition metal complexes as frustrated Lewis pairs - a computational investigation - Pal, Amrita; Vanka, Kumar (Dalton Transactions, 2013)
There has been considerable interest in recent times to develop transition metal complex systems that can demonstrate metal-ligand cooperativity. It has recently been shown (Wass et al., J. Am. Chem. Soc., 2011, 133, 18463) that early transition metals can cooperate with ligands carrying phosphines as pendant groups, working as metal analogues to frustrated Lewis pairs (FLPs) to mediate in a variety of important reactions. What the current work attempts to do is to show how this concept of metal containing FLPs can be expanded to include late transition metal complexes as well: complexes that have been modified from existing systems that serve as efficient catalysts for homogeneous polymerization. A modified palladium complex has been considered in this regard as an example of a potential late transition metal FLP and studied with full quantum mechanical calculations. The calculations indicate that this complex would be effective at catalyzing ammonia borane dehydrogenation. The possibility of competing side reactions such as reductive elimination have also been considered, and it has been found that such processes would also yield stable products which could act as an FLP in catalyzing reactions such as the dehydrogenation of ammonia borane. The current work therefore expands the scope of metal containing FLPs to include late transition metals and demonstrates computationally the potential of such complexes for exhibiting metal-ligand cooperativity.

Can silylenes rival transition metal systems in bond-strengthening pi-back donation? a computational investigation - Pal, Amrita; Vanka, Kumar (Chemical Communications, 2014)
Full quantum chemical calculations with density functional theory (DFT) show that bond-strengthening back-donation to a pi-diborene, recently discovered for transition metal systems (Braunschweig and co-workers, Nat. Chem., 2013, 5, 115-121), would be just as favored for Main Group silylene complexes. This result not only shows the range and applicability of the bond-strengthening back-bonding interaction, but also showcases the capacity of silylene complexes to do new chemistry, such as the cooperative activation of carbon monoxide and carbon dioxide.

Small molecule activation by constrained phosphorus compounds: insights from theory - Pal, Amrita; Vanka, Kumar (Inorganic Chemistry, 2016)
An exciting new development in main group chemistry has been the use of a constrained, flat, phosphorus-based complex to mediate in reactions such as the dehydrogenation of ammonia borane (AB), and the activation of the NH bond in primary amines. Its importance is based on the fact that it shows that main group compounds, when properly designed, can be as effective as transition metal complexes for doing significant chemical transformations. What the current computational study, employing density functional theory (DFT), reveals is that a common, general mechanism exists that accounts for the behavior of the flat phosphorus compound in the different reactions that have been experimentally reported to date. This mechanism, which involves the mediation by a base as a proton transfer agent, is simpler and energetically more favorable than the previous mechanisms that have been proposed for the same reactions in the literature. It is likely that the knowledge gained from the current work about the chemical behavior of this phosphorus compound can be utilized to design new constrained phosphorus-based compounds.

Exploring the effect of hydroxylic and non-hydroxylic solvents on the reaction of [(VO)-O-IV(beta-diketonate)2] with 2-aminobenzoyl-hydrazide in aerobic and anaerobic conditions - Biswas, Nirmalendu; Patra, Debashis; Mondal, Bipul; Bera, Sachinath; Acharyya, Swarnali; Biswas, Anup Kumar; Mukhopadhyay, Titas Kumar; Pal, Amrita; Drew, Michael G. B.; Ghosh, Tapas (Dalton Transactions, 2017)
Refluxing [(VO)-O-IV(beta-diketonate)(2)], namely [(VO)-O-IV(acetylacetonate)(2)] and [(VO)-O-IV(benzoylacetonate)(2)], separately with an equivalent or excess amount of 2-aminobenzoylhydrazide (ah) in laboratory grade (LG) CH3OH in aerobic conditions afforded non-oxidovanadium(IV) and oxidovanadium(V) complexes of the type [V-IV(L-1)(2)] (1), [(VO)-O-V(L-1)(OCH3)](2) (3) and [V-IV(L-2)(2)] (2), and [(VO)-O-V(L-2)(OCH3)] (4), respectively. (L-1)(2-) and (L-2)(2-) represent the dianionic forms of 2-aminobenzoylhydrazone of acetylacetone (H2L1) and benzoylacetone (H2L2), respectively, (general abbreviation, H2L), which was formed by the in situ condensation of ah with the respective coordinated [beta-diketonate] in medium-to-good yield. The yield of different resulting products was dependent upon the ratio of ah to [(VO)-O-IV(beta-diketonate)(2)]. For example, the yield of 1 and 2 complexes increased significantly associated with a decrease in the amount of 3 and 4 with an increase in the molar ratio of ah. Upon replacing CH3OH by a non-hydroxylic solvent, LG CHCl3, the above reaction yielded only oxidovanadium(V) complexes of the type [(VO)-O-V(L-1)(OH)](2) (5), [(VO)-O-V(L-2)(OH)] (6) and [(V2O3)-O-V(L)(2)] (7, 8) whereas, upon replacing CHCl3 by another non-hydroxylic solvent, namely LG CH3CN, only the respective [(V2O3)-O-V(L)(2)] (7, 8) complex was isolated in 72-78% yield. However, upon performing the above reactions in the absence of air using dry CH3OH or dry CHCl3, only the respective [V-IV(L)(2)] complex was obtained, suggesting that aerial oxygen was the oxidising agent and the type of pentavalent product formed was dependent upon the nature of solvent used. Complexes 3 and 4 were converted, respectively, to 7 and 8 on refluxing in LG CHCl3 via the respective unstable complex 5 and 6. The DFT calculated change in internal energy (Delta E) for the reactions 2[(VO)-O-V(L-2)(OCH3)] + 2H(2)O -> 2[(VO)-O-V(L-2)(OH)] + 2CH(3)OH and 2[(VO)-O-V (L-2)(OH)] -> [(V2O3)-O-V(L-2)(2)] + H2O was, respectively, +3.61 and -7.42 kcal mol(-1), suggesting that the [(VO)-O-V(L-2) (OH)] species was unstable and readily transformed to the stable [(V2O3)-O-V(L-2)(2)] complex. Upon one-electron reduction at an appropriate potential, each of 7 and 8 generated mixed-valence [(L) (VO)-O-V-(mu-O)-OVIV(L)]species, which showed valence-delocalisation at room temperature and localisation at 77 K. Some of the complexes showed a wide range of toxicity in a dose-dependent manner against lung cancer cells comparable with that observed with cis-platin.
Keywords: Effective Core Potentials; Lung-cancer cells; Molecular-Orbital Methods; Non-oxido vanadium(iv); Non-Oxo; Oxovanadium(iv) Complexes; Tridentate ono ligand; Ray crystal-structure; Trigonal-prismatic Co-ordination; V-IV complex